Cutaneous complications associated with breast augmentation: A review - S. Chopra, MBBS, BSc, MRCS; D. Marucci, MBBS, BA, PhD, FRACS (Wolters Kluwer, 2019)
Breast augmentation is one of the most popular and safe cosmetic procedures performed by plastic surgeons worldwide. Although breast implants are available in a number of different materials, silicone-filled implants remain the most common type. However, prior to the development of breast implants, various materials were injected into the soft tissues of the breasts to increase breast volume, which caused cutaneous complications and disfigurement. This review details the history of breast augmentation, the current methods used in augmentation surgery, and associated cutaneous complications. Keywords: Plastic surgery, reconstructive surgery